HIF1α Modulates Cell Fate Reprogramming Through Early Glycolytic Shift and Upregulation of PDK1–3 and PKM2. (13th January 2014) - Prigione, Alessandro; Rohwer, Nadine; Hoffmann, Sheila; Mlody, Barbara; Drews, Katharina; Bukowiecki, Raul; Blümlein, Katharina; Wanker, Erich E.; Ralser, Markus; Cramer, Thorsten; Adjaye, James
Abstract : Reprogramming somatic cells to a pluripotent state drastically reconfigures the cellular anabolic requirements, thus potentially inducing cancer-like metabolic transformation. Accordingly, we and others previously showed that somatic mitochondria and bioenergetics are extensively remodeled upon derivation of induced pluripotent stem cells (iPSCs), as the cells transit from oxidative to glycolytic metabolism. In the attempt to identify possible regulatory mechanisms underlying this metabolic restructuring, we investigated the contributing role of hypoxia-inducible factor one alpha (HIF1 α ), a master regulator of energy metabolism, in the induction and maintenance of pluripotency. We discovered that the ablation of HIF1 α function in dermal fibroblasts dramatically hampers reprogramming efficiency, while small molecule-based activation of HIF1 α significantly improves cell fate conversion. Transcriptional and bioenergetic analysis during reprogramming initiation indicated that the transduction of the four factors is sufficient to upregulate the HIF1 α target pyruvate dehydrogenase kinase (PDK) one and set in motion the glycolytic shift. However, additional HIF1 α activation appears critical in the early upregulation of other HIF1 α -associated metabolic regulators, including PDK3 and pyruvate kinase (PK) isoform M2 (PKM2), resulting in increased glycolysis and enhanced reprogramming. Accordingly, elevated levels of PDK1, PDK3, and PKM2 and reduced PK activity could be observed in iPSCs and human embryonic stem cells in the undifferentiated state. Overall, the findings suggest that the early induction of HIF1 α targets may be instrumental in iPSC derivation via the activation of a glycolytic program. These findings implicate the HIF1 α pathway as an enabling regulator of cellular reprogramming. Stem Cells 2014;32:364–376